La metodología de maría Montessori y su incidencia del material didáctico en el aula taller de la carrera de educación Parvularia de la universidad técnica de Cotopaxi en el sector Eloy Alfaro del cantón Latacunga de la provincia de Cotopaxi periodo 2011-2012 - Reyes Venegas, Mayra Elizabeth (2014)
The research contains important aspects to improve the teaching and learning process with the implementation of the classroom workshop with the teaching materials of the Montessori teacher for students of Early Childhood Education from the Technical University of Cotopaxi taking advantage from one of the most acceptance activities for children as it is through the game. This work was implemented in the classroom workshop of the Technical University of Cotopaxi the Latacunga canton, after detect the problem in the students’ acquisition of new knowledge, setting clear objectives that can be completed with the methodology of Montessori. It is based on theoretical and practical way through Educators specialized information obtained in the research topic, which was important for the production of educational materials Montessori methodology to invigorate the students. The validity of this work is based on the weaknesses that are observed to develop research students of Early Childhood Education by the lack of appropriate training material which was a difficulty when teachers implemented the teaching process. We found the solution to form a classroom workshop applying the methodology and teaching materials Maria Montessori, and after that to use something new knowing is more fun and meaningful for classes.